Brain Oxygen Extraction and Metabolism in Pediatric Patients With Sickle Cell Disease: Comparison of Four Calibration Models - Lin, Zixuan; McIntyre, Tiffany; Jiang, Dengrong; Cannon, Alicia; Liu, Peiying; Tekes, Aylin; Casella, James F.; Slifer, Keith; Lu, Hanzhang; Lance, Eboni (Frontiers in Physiology, 2022)
Sickle cell disease (SCD) is an inherited hemoglobinopathy with an increased risk of neurological complications. Due to anemia and other factors related to the underlying hemoglobinopathy, cerebral blood flow (CBF) increases as compensation; however, the nature of alterations in oxygen extraction fraction (OEF) and cerebral metabolic rate of oxygen (CMRO2) in SCD remains controversial, largely attributed to the different calibration models. In addition, limited studies have been done to investigate oxygen metabolism in pediatric patients. Thus, this study used a non-invasive T2-based MR oximetry, T2-Relaxation-Under-Spin-Tagging (TRUST) MRI, to measure oxygen homeostasis in pediatric patients with SCD using four different calibration models and examined its relationship to hematological measures. It was found that, compared with controls, SCD patients showed an increased CBF, unchanged total oxygen delivery and increased venous blood T2. The results of OEF and CMRO2 were dependent on the calibration models used. When using sickle-specific, hemoglobin S (HbS) level-dependent calibration, there was a decreased OEF and CMRO2, while the bovine model showed an opposite result. OEF and CMRO2 were also associated with hemoglobin and HbS level; the direction of the relationship was again dependent on the model. Future studies with in vivo calibration are needed to provide more accurate information on the T2-Yv relationship.